Black Men Writing, Reflecting, and Discovering Self: Personal Narrative Essays of College-aged African American Men at an All-male Historically Black College or University (HBCU) - Norment, Nathaniel (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2023)
Personal narratives are studied in many disciplines, but theoretical analysis of the personal narrative in composition classes has lagged behind the research. This qualitative study examines the personal narratives of thirty Black college-aged men. This study presents the feelings and thoughts of Black males through their personal stories and perspectives; in the study, they detail their life experiences. The narratives were analyzed for elements of narrative discourse, which include (1) Thesis; (2) Transitions; (3) Use and Evaluation of Sources; (4) Audience, Tone, and Rhetorical Appeals; (5) Organization; (6) Claims, Warrants, and Support; (7)Paraphrases, Direct Quotes, and Summary; (8) In-text Citations and Works Cited Page; (9) Style and Syntax; and (10) Mechanics (see scoring procedures). Each narrative was analyzed according to the criteria described in the Personal Narrative Rubric; the number of elements was counted for each category. The researcher recommends additional narrative studies of Black men in different age groups, educational backgrounds, social and economic levels, and geographical regions.